Mom, why dont you just look for a new good daddy? Womens lived experience in an abusive marriage - Nurhayati, Elly (Journal of Educational, Health and Community Psychology, 2012)
This study aimed to understand womens experiences of domestic violence and their decision to terminate the abusive marriage in Yogyakarta. Criterion sampling of three woman survivor of domestic violence was performed. These consented to be interviewed and a semi structure interview guide was used. The women shared their life experiences since the dating time up to the time after divorce. A phenomenological approach was employed to analyze the data, to explore, share, and validate their feelings and insights on their life experiences. From this study numerous factors that facilitated as well as hindered the women to terminate their abusive relationships, and the dynamics of the transition process were identified. The womens experiences reflect the complexity of domestic violence. The womens transformation from victims, meaning women living under the authorities, into survivors, meaning woman with self-autonomy, is demonstrated through their stories. The complexity of domestic violence among Indonesia women is only a little known. By comprehending the complexity of domestic violence, a more visible and practical programs to address the national commitment to improve the Indonesian womens situation can be developed.